Features of Development of Movement Coordination in Young Athletics - Ibragimov Alisher Karomatovich; Tolibova Nilufar Rakhmat qizi (International Journal of Formal Education, 2024)
In this article, it is explained that the methodology of selecting children for complex athletics, which includes an integral indicator of speed, speed-power abilities, as well as functional and coordination qualities, is effective.